'I was exhausted trying to figure it out': The experiences of females receiving an autism diagnosis in middle to late adulthood. (January 2020) - Leedham, Alexandra; Thompson, Andrew R; Smith, Richard; Freeth, Megan
Females often receive autism spectrum condition diagnoses later than males, leaving needs misunderstood. This study aimed to explore the lived experiences of female adults diagnosed with an autism spectrum condition in middle to late adulthood. Eleven autistic females diagnosed over the age of 40 years completed semi-structured interviews, analysed using Interpretative Phenomenological Analysis. Four superordinate themes emerged: A hidden condition (pretending to be normal and fitting in; mental health and mislabelling), The process of acceptance (initial reactions and search for understanding; re-living life through a new lens), The impact of others post-diagnosis (initial reactions; stereotyped assumptions), and A new identity on the autism spectrum (negotiating relationships, connections and community; changing well-being and views of the self; the meaning of diagnosis). Findings highlight several factors not previously identified that affect late diagnosis in females, including widespread limited understandings of others. Diagnosis was experienced by several participants as facilitating transition from being self-critical to self-compassionate, coupled with an increased sense of agency. Participants experienced a change in identity that enabled greater acceptance and understanding of the self. However, this was painful to adjust to at such a late stage.